Data breach worries: a special report - Lim, Cian Yai; Zulhuda, Sonny (HCK Media, 2014)
Australian company’s recent acquisition of JobStreet’s assets raises the question of whether Malaysia is exposing its sensitive data to foreign companies. While mergers and acquisitions (M&As) are part of doing business and cannot be avoided or controlled by the authorities, are Malaysian companies inevitably exposing data deemed sensitive to foreigners? To what extent are these companies and even government agencies revealing strategic information by allowing them access to data that carry financial, economic and security value?